Assessment of Differential Item Functioning of Basic Education Certificate Examination Mathematics Multiple Choice Items - OLUTOLA, Adekunle Thomas; IHECHU, Kelechi Joshua Princewill; NURADDEEN, Yusuf Galadanchi (Ilorin Journal of Education, 2023)
The study assessed the Differential Item Functioning of 2020 Basic Education Certificate Examination (BECE) Mathematics multiple choice test items in Dutsin-Ma Education Quality Assurance, Katsina State, Nigeria. The study adopted Descriptive Survey research design and Ex-Post-Facto research design. The population of the study is 4,881 junior secondary school students in Dutsin-Ma Educational Quality Assurance Zone. A multi-stage sampling technique was used for the study to obtain a sample size of 525 mathematics junior secondary school students (JSS III) which were proportionately drawn from the 10 selected secondary schools that constituted the sample size of the study. The instrument used for data collection was 2020 Basic Education Certificate Examination (BECE) multiple choice mathematics items conducted in 2019/2020 academic sessions with reliability indices of 0.75. Data obtained for the study were analyzed using the Scheuneman modified Chi-square statistic to answer all the research questions and chi-square test statistic was employed in testing the null hypotheses at 0.05 level of significant. The results revealed that Basic Education Certificate Examination (BECE) multiple choice mathematics items used in 2020 examinations contain test items that significantly functioned differentially for testees on the basis of gender. Based on the finding, it was recommended that test developers, ministry of education and examination bodies should ensure that Mathematics multiple choice test items are free from differential item functioning (DIF) for adequacy of test credibility and civility.